The Evolutionary Relationship between Alternative Splicing and Gene Duplication - Iñiguez, Luis P.; Hernández, Georgina (Frontiers in Genetics, 2017)
Abstract The protein diversity that exists today has resulted from various evolutionary processes. It is well known that gene duplication along with the accumulation of mutations are responsible, among other factors, for an increase in the number of different proteins. The gene structure in eukaryotes requires the removal of non-coding sequences, introns, to produce mature mRNAs. This process, known as cis-splicing, referred to here as splicing, is regulated by several factors which can lead to numerous splicing arrangements, commonly designated as alternative splicing. Alternative splicing, producing several transcripts isoforms form a single gene, also increases the protein diversity. However, the evolution and manner for increasing protein variation differs between alternative splicing and gene duplication. An important question is how are patterns of alternative splicing affected after a gene duplication event. Here, we review the current knowledge of alternative splicing and gene duplication, focusing on their evolutionary relationship. These two processes are now considered the main contributors to the increasing protein diversity and therefore their relationship is a relevant, yet understudied, area of evolutionary study.